Application Of Data Mining To Determine The Amount Of Production Using The K-Means Method (Case Study At Pt. Coca Cola Distribution Indonesia Bengkulu) - Mardiana, Yessi; Kalsum, Toibah Umi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2022)
This study applies Data Mining using the Clustering method to determine the amount of production based on the level of product sales at PT. Coca Cola Distribution Indonesia Bengkulu branch. The algorithm used is K-Means Clustering, where data grouped based on the same characteristics will be included in the same group and the data sets entered into the groups do not overlap. The information displayed is in the form of product data groups based on the level of sales, so that it is known the amount of production at PT. Coca Cola Distribution Indonesia which is adjusted to product clusters with high, medium and low sales levels, resulting in product clusters that could be utilized by PT. Coca Cola Distribution Indonesia in determining the number of production of the next product